Commentary on experiential learning: changing student attitudes towards learning disability: how can we reduce exclusion further?. Issue 3 (2nd July 2014) - Harding, Celia
Abstract : Purpose: – The purpose of this paper is to provide some thoughts following on from reading: "Experiential learning: changing student attitudes towards learning disability". Design/methodology/approach: – This commentary outlines some considerations for the continued development of using service users in tertiary education as educators. Findings: – The literature is not clear on the involvement of people with more profound and multiple learning disabilities, or for those who do not use much spoken language in tertiary level teaching. Originality/value: – A further cultural shift is needed to ensure that all people with learning disabilities regardless of their communication style have the opportunity to share their experiences within a teaching and learning context.